THE EFFECT OF LIQUIDITY AND SALES GROWTH ON CAPITAL STRUCTURE WITH PROFITABILITY AS A MODERATING VARIABLE - Edi Supriyono; Novita Chantika Putri (CV. Adiba Aisha Amira, 2025)
This study aims to test and analyze the influence of liquidity and sales growth on capital structure with profitability as a moderating variable. The research object used in this study is a manufacturing companies listed in the Indonesia Stock Exchange period 2018-2022. The number of samples selected using the purposive sampling method was 394 data from 160 companies. This study used Moderated Regression Analysis (MRA) supported by Eviews 12 software. Based on the result of the study, it was found that liquidity has a significant negative eflect on capital structure, sales growth has a significant positive eflect on capital structure, profitability cannot moderate the eflect of liquidity on capital structure, and profitability cannot moderate the eflect of sales growth on capital structure.